(untitled) (Hà Nội, 1996)
Contents: The relationship between the mangrove ecosystem and aquaculture; techniques on planting tending and management mangroves; the socio-economic situation in mangrove areas.
Keywords: Aquaculture,Nuôi trồng thuỷ sản; Vietnam,Việt Nam